Monitoring and evaluation of the dissemination of the agroclimatic bulletin to farmers in Guatemala during 2025 - Bonilla, Melissa; Zapata Caldas, Emmanuel; Navarro, Carlos Eduardo; Orrego, Elmer; Lopez, Pedro (2025)
A monitoring and evaluation process has been conducted during 2025 in Chimaltenango and Santa Rosa, this brief is an extract of the Report "​From design to action: Evidence of implementation and scaling up of agroclimatic services in Guatemala" The monitoring and evaluation process has aimed to analyze the scope, effectiveness, understanding and use of the community agroclimatic bulletin, as well as its influence on agricultural decision-making and community circulation of information. This exercise has had the participation of the Private Institute for Climate Change Research (ICC) in Chimaltenango and the Ministry of Agriculture and Livestock (MAGA) in Santa Rosa, has covered the departments of Chimaltenango and Santa Rosa and has been developed during the period between August and September 2025.